O si mesmo enquanto uma ontologia partida - Silva, Jeferson Flores Portela da (2021)
This thesis deals with the following problem: the self as a broken ontology. The research is based on the general thesis that there are several ontological notions in Paul Ricoeur's work. However, these notions are spread over different problems and works; thus, there is no systematization of the same. Even among commentators, there is a difference in the approach on the theme, including in the thesis. A divergence in some interpretations of Ricoeur's ontology: onto-poetics, onto-action, onto-anthropological, and attestation as an ontology of ipseity (Ricoeur's thesis defended in Soi-même comme un autre). Moreover, we note that from the methodological point of view, we have tried in the research to discuss these ways of interpreting the ontological question. But also, to reconstruct some steps that we consider important for the understanding of the thesis, such as the discussion exposed by Ricoeur about the voluntary and involuntary. Bearing that in mind, we point out the influence suffered by the philosopher from the ideas of authors such as Gabriel Marcel and Maine from Biran regarding the problem of the body and carnality. Thus, the investigation was based on a reconstruction of the tension between, I think, therefore I am, exalted by Descartes, and anti-I think; therefore, I am, in the sense of Nietzsche's philosophy until we arrive at the Hermeneutics of the self. Afterward, the problem was focused on the plurality of personal identity with its modes of permanence in time. In the end, the problem is presented in its totality by a discussion about the ontology of the self. As a matter of fact, is it possible to think of a broken ontology? And in what way does Ricoeur appropriate and deny ontologies such as the Aristotelian, Heideggerian, and Spinosa´s one? Would these not be sufficient for the ontological status of the subject in Ricoeur? These questions are part of our ultimate problems, by which the selfhood of the self will be attested as the ontology of the reflective subject. However, we still must ask about the onto-anthropological place of this subject crossed by alterity. Because of this itinerary, our reference literature concerning the philosopher Paul Ricoeur consists of the Le volontaire et l‟involontaire, Finitude et culpabilité, Le conflit des interprétations, Temps et récit e Soi-même comme un autre. Starting with the, Le volontaire et l‟involontaire the project of the phenomenology of the will is initially exposed, concerning the categories of voluntary and involuntary, which will structure the will of man in the phenomenology of acting. Finitude et culpabilité, Le conflit des interprétations e Temps et récit will guide us in understanding the ontological problems in the face of the obscurity that arises from the narrative and philosophy of action, culture, and other forms of alterity that mediate with the self in a sense of completeness of I think; therefore, I am (a theme that will be treated in session 2 of the thesis). It is with Soi-même comme un autre that we will deepen the problem of this research regarding the ontological problem. The latent question will be that of attestation as to the ontology of ipseity. In general lines, the hermeneutics of the self is long, and in this, we will understand how the self cannot have the same direction in a short way like Dasein.